Desenvolvimento estrutural e implicações metabólicas no sistema Lonchocarpus cultratus-Cecidomyiidae - Aline Yasko Marinho Suzuki (2015)
Lonchocarpus cultratus (Vell.) Azevedo & Lima (Fabaceae) hosts leaflet galls induced by an unidentified species of Lopesia sp. (Diptera: Cecidomyiidae). Cell fates are strongly altered during gall development. The neoformed stomata, the presence of live sclerenchyma cells surrounding the nutritive tissue, and the processes of cell hypertrophy and tissue hyperplasia are the most important structural features involved in gall development. From the biochemical point of view, the galling Cecidomyiidae stimulates the production of triterpenes, and suppress the accumulation of starch and free steroids in gall tissues. Synthesis, blockage and spatial compartmentalization of metabolites provide specific functionalities to the newly formed tissue, ensuring protection and nutrition to the galling insect. The accumulation of proteins in nutritive cells indicates that these metabolites are used in the diet of the galling Cecidomyiidae. Growth regulators such as the acid-indole-3-acetic acid (IAA), (poly)phenols and flavonoids are strongly detected in the sites of hypertrophied cells, and restricted to a small group of cells in hyperplasic sites, corroborating the associate roles of these compounds in gall development. The accumulation of reactive oxygen species (ROS) and IAA in the cell walls may cause acidification and, consequently, the loosening of the cellulose microfibrils that influence the direction of cell elongation. Another component of the cell wall, the pectins, can affect cell expansion by controlling the flexibility and rigidity. The redirection of cell functions occurs mainly in the nutritive tissue, where the pectin and protein dynamics of the cell wall converges to maintain porosity, and guarantee a higher flow of nutrients to the galling insect. At the early and intermediate stages of leaflet and gall development, pectin and protein epitopes related to flexibility are detected, while at the final stages, the cell wall compounds guarantee stiffness.